Indications for red blood cell transfusion in cardiac surgery: a systematic review and meta-analysis - Patel, Nishith N; Avlonitis, Vassilios S; Jones, Hayley E; Reeves, Barnaby C; Sterne, Jonathan A C; Murphy, Gavin J (The Lancet. Haematology, 2015)
Good blood management is an important determinant of outcome in cardiac surgery. Guidelines recommend restrictive red blood cell transfusion. Our objective was to systematically review the evidence from randomised controlled trials and observational studies that are used to inform transfusion decisions in adult cardiac surgery. We did a systematic review by searching PubMed, Embase, Cochrane Library, and DARE, from inception to May 1, 2015, databases from specialist societies, and bibliographies of included studies and recent relevant review articles. We included randomised controlled trials that assessed the effect of liberal versus restrictive red blood cell transfusion in patients undergoing cardiac and non-cardiac surgery, and observational studies that assessed the effect of red blood cell transfusion compared with no transfusion on outcomes in adult cardiac patients after surgery. We pooled adjusted odds ratios using fixed-effects and random-effects meta-analyses. The primary outcome was 30-day mortality. We included data from six cardiac surgical randomised controlled trials (3352 patients), 19 non-cardiac surgical trials (8361 patients), and 39 observational studies (232,806 patients). The pooled fixed effects mortality odds ratios comparing liberal versus restrictive transfusion thresholds was 0.70 (95% CI 0.49-1.02; p=0.060) for cardiac surgical trials and 1.10 (95% CI 0.96-1.27; p=0.16) for trials in settings other than cardiac surgery. By contrast, observational cohort studies in cardiac surgery showed that red blood cell transfusion compared with no transfusion was associated with substantially higher mortality (random effects odds ratio 2.72, 95% CI 2.11-3.49; p<0.0001) and other morbidity, although with substantial heterogeneity and small study effects. Evidence from randomised controlled trials in cardiac surgery refutes findings from observational studies that liberal thresholds for red blood cell transfusion are associated with a substantially increased risk of mortality and morbidity. Observational studies and trials in non-cardiac surgery should not be used to inform treatment decisions or guidelines for patients having cardiac surgery. None.